2001
DOI: 10.1007/s11746-001-0391-z
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of phytosterols in a test food system

Abstract: The oxidative stability of phytosterols in canola, coconut, peanut, and soybean oils was examined under simulated frying conditions of 100, 150, and 180°C for 20 h. The degree of oxidative decomposition was assessed by the loss of phytosterols, accumulation of phytosterol oxides, and the change in fatty acid profiles. The phytosterol oxides produced in the oils were identified using mass spectroscopy. Oils with higher levels of polyunsaturated fatty acids showed greater amounts of sterol loss; however, the ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 19 publications
2
41
0
1
Order By: Relevance
“…A possible explanation of these results could be the degradation of sterols into other compounds and the destruction of sterol oxides after their formation owing to the use of prolonged drastic heating conditions. Oehrl et al (44) found that, as the temperature increased, fewer phytosterol oxides were recovered, implying that the extreme heat treatments resulted in the total degradation of sterol complexes. Sterols may have also been broken down to components smaller than oxides, which were not detectable by GC-MS.…”
Section: Resultsmentioning
confidence: 99%
“…A possible explanation of these results could be the degradation of sterols into other compounds and the destruction of sterol oxides after their formation owing to the use of prolonged drastic heating conditions. Oehrl et al (44) found that, as the temperature increased, fewer phytosterol oxides were recovered, implying that the extreme heat treatments resulted in the total degradation of sterol complexes. Sterols may have also been broken down to components smaller than oxides, which were not detectable by GC-MS.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding oxidation that affects the side chain, whereas a small content on 25-hydroxycholesterol could be noticed, no 25-hydroxystigmasterol was detected in the sample. Although the theoretically calculated enthalpies for C25 would indicate a more labile bond for stigmasterol than for other sterols (and the subsequent higher formation of 25-hydroxycholesterol) [31], no formation of this compound under heating conditions of stigmasterol solved in vegetable oils has been previously reported [15].…”
Section: Oxysterols Distributionmentioning
confidence: 90%
“…Furthermore, the presence of the surrounding lipids and their unsaturation degree exert some kind of effect, affecting the pattern of resulting oxidation products and also modulating the intensity and rate of oxidative reactions [15][16][17][18]. Additionally, both synthetic and natural antioxidants have presented promising results against sterol oxidation, being phenolic compounds and some vitamins some of the most studied compounds [19][20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As can be noted, the gap increased with increasing the frying time for both frying applications. Oehrl et al (2001) noticed a large "gap" in their PS oxidation study, in which drastic heating conditions were applied. In the case of PS compounds, it is also possible that the "gap" partly originates from the formation of steradienes and -trienes, i.e., steroidal hydrocarbons with two or three double bonds in the ring structure.…”
Section: The Formation Of Uncharacterized Popmentioning
confidence: 99%